Meio ambiente e interdisciplinaridade nas escolas Públicas Estaduais de Rialma - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
Nowadays, environmental issues have been focus in discussions around the world. Consequently, to question the way how to view this thematic in schools through Environmental Education is necessary. This research had an objective to analyze the practice of Environmental Education in public schools in Rialma, Goiás. The students of eighthy grade from school Câmara Filho are involved and the subjects involved are Science and Math, from two schools existing in Rialma. It was used in this research a qualitative one, enriched with a field research. For the development, it was done a bibliographic study in order to have a better theoric result in the theme and conceptions from the authors: Genebaldo Freire Dias (2004), Marília Freitas de Campos Tozoni-Reis (2004), Antonio Gramsci (1995) e Paulo Freire (1981, 1983, 1996) e Ivani Fazenda (1998, 2004). The second stage was to collect informations through a questionaire opened and closed to the research. For that, it looked for authors that show reflections in Environmental Education, in Paulo Freire’s pedagogy and a historic dialect method. The analyzes of results revealed that the students undestand the concept of environment, however without relation of culture and social dimensions. In this order is important to show the students a view contextualized, understanding the multiplicity and amplitude, in this way they could be capable to think about their atitude and interfere in the environment. To the teachers is perceptive a lack of formation in Environmental Education. The proposal in this way will be the elaboration of a game that covers a interdisciplinary knowledge about environment to the students of the schools.
Keywords: Meio ambiente; Ensino; Interdisciplinaridade; Paulo Freire; Método histórico dialético; Environment; Teaching; Interdisciplinarity; Paulo Freire; Historic dialect method; CIENCIAS BIOLOGICAS